2011
DOI: 10.1007/s10152-011-0276-x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal differentiation and speciation in sister-species of Grammatidae (Perciformes) from the Western Atlantic

Abstract: In the tropical Atlantic, the ichthyofauna between the coast of Brazil and the Caribbean regions, divided by the Amazon barrier, is very similar presenting several geminate species, including Gramma brasiliensis, endemic in Brazil, and its Caribbean counterpart Gramma loreto. Morphological and molecular studies have helped establish evolutionary patterns that sister-species of these two marine habitats are subjected to. However, their chromosomal characteristics are only beginning to be better characterized. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…In fact, C. lugubris that are GC-rich in most chromosomes show the most cytogenetic differences among the 3 species. High GC+ content dispersed throughout all chromosomes, although uncommon, has been identified in some marine families such as Tetraodontidae and Grammatidae (Martinez et al, 2011;Molina et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, C. lugubris that are GC-rich in most chromosomes show the most cytogenetic differences among the 3 species. High GC+ content dispersed throughout all chromosomes, although uncommon, has been identified in some marine families such as Tetraodontidae and Grammatidae (Martinez et al, 2011;Molina et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Cioffi et al, 2009). Although equilocation between Ag-NORs and 18S rDNA is normally expected (Nirchio et al, 2007;Molina et al, 2011), numerous cases of lack of correspondence between these sites have been reported (e.g. Vicari et al, 2003), justifying the use of both methodologies for a more thorough study of the presence and distribution of nucleolus organizer regions in the karyotypes.…”
Section: Ag-nors and Ribosomal Sites As Chromosomal Markers In Bodianusmentioning
confidence: 93%
“…The species Bodianus rufus, B. pulchellus, and B. insularis exhibit an atypical chromosomal region, exceptionally decondensed and argentophilic, but without affinity with 18S rDNA probes and not a GC-rich region (Molina et al, 2012a). On the contrary, in the species now analyzed, the heterochromatin has a predominantly centromeric distribution, seemingly little variable, with low intra-and interspecific discriminatory power.…”
Section: Discussionmentioning
confidence: 90%